Geometry verbal skill of field dependent-independent students in junior high school according to van hiele thinking level - M Misnasanti; A Mahmudi (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This research aimed to describe the geometry verbal skill of FD-FI students in Junior High School at level 1, level 2 and level 3 according to Van Hiele Theory. This research was a survey. This research was conducted for grade 8 students of junior high schools. The samples were selected using proportionate stratified random sampling technique which was a combination of stratified sampling technique and proportional sampling technique followed by random sampling technique. This technique was used to determine the sample proportionately for each strata. The samples consisted of 4 representative high strata schools. The data were collected using tests and interview. Data analysis technique consists of data reduction, data display, and data conclusion. The result showed that: (1) FI students level 1, 2 and 3 get a better result than FD students to associate the correct name with a given properties and to define a figure accurately and concisely by showing interrelationships between figures, (2) FD students is better than FI students to define a figure accurately with various properties, (3) From 103 students, there is only one FI student at level 3 can answer definition of figure perfectly.